2018
DOI: 10.1302/2046-3758.71.bjr-2017-0323
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers in periprosthetic joint infections

Abstract: ObjectivesThe diagnosis of periprosthetic joint infection (PJI) is difficult and requires a battery of tests and clinical findings. The purpose of this review is to summarize all current evidence for common and new serum biomarkers utilized in the diagnosis of PJI.MethodsWe searched two literature databases, using terms that encompass all hip and knee arthroplasty procedures, as well as PJI and statistical terms reflecting diagnostic parameters. The findings are summarized as a narrative review.ResultsErythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 69 publications
2
71
1
Order By: Relevance
“…Metal on metal bearings constitute another challenge due to the difficulty of establishing the correct diagnostic thresholds for inflammatory markers in the serum and synovial fluid samples. In fact, a number of studies suggested that CRP and ESR are not reliable alone in diagnosing PJI in metal on metal cases and that the synovial fluid WBC count can frequently be falsely positive and, therefore, should be relied on only if a manual count is done and a differential can be performed [12,51,52]. The ICM also suggests being cautious whilst applying its diagnostic criteria for PJIs in metal on metal cases for the same reasons [12].…”
Section: Discussionmentioning
confidence: 99%
“…Metal on metal bearings constitute another challenge due to the difficulty of establishing the correct diagnostic thresholds for inflammatory markers in the serum and synovial fluid samples. In fact, a number of studies suggested that CRP and ESR are not reliable alone in diagnosing PJI in metal on metal cases and that the synovial fluid WBC count can frequently be falsely positive and, therefore, should be relied on only if a manual count is done and a differential can be performed [12,51,52]. The ICM also suggests being cautious whilst applying its diagnostic criteria for PJIs in metal on metal cases for the same reasons [12].…”
Section: Discussionmentioning
confidence: 99%
“…Both the CRP and ESR, which are considered as speci c indicators of infection, were shown to be highly elevated in the PJI group and to gradually decline postoperatively [20,22]. The sensitivity of CRP for diagnosing PJI has been reported to range from 74 to 94%, whereas its speci city ranged from 20 to 100%, with different predictive cutoffs [20,[22][23][24][25]. On the other hand, the sensitivity and speci city of ESR were reported to vary from 42 to 94%, and 33 to 90%, respectively [17,[22][23][24]26].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of CRP for diagnosing PJI has been reported to range from 74 to 94%, whereas its speci city ranged from 20 to 100%, with different predictive cutoffs [20,[22][23][24][25]. On the other hand, the sensitivity and speci city of ESR were reported to vary from 42 to 94%, and 33 to 90%, respectively [17,[22][23][24]26]. Compared with these reports, in our study, the sensitivity for CRP and ESR in predicting PJI was shown to be 62.50% and 59.38%, while the speci city was 83.12% and 80.52%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, D-dimer was reported by Qin et al as a promising biomarker for diagnosing PJI [28] while Xu et al demonstrated that D-dimer had limited value [24]. Nonetheless, both biomarkers have a lower diagnostic performance than ESR, CRP and plasma brinogen which have been reported repeatedly to have better diagnostic power (in terms of AUC, sensitivity, speci city) in the diagnosis of PJI [5,8,22,23,29]. However, the AUC of globulin and A/G ratio was larger than 0.7, indicating an acceptable diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…In ammation and infection play a vital role in the process of developing PJI and various markers related to these processes such as the C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) have been investigated for their ability to predict PJI [8,9]. Globulin, an easily accessible and reliable biomarker in the basic metabolic panel, has proven to be a critical marker associated with in ammation and infection [10].…”
Section: Introductionmentioning
confidence: 99%